Contributions of Corporate Social Responsibility on Infrastructure Improvements in Public Primary Schools in Tanzania - Maduhu, Mgema Masunga; Komba, Cyril Kalembana; Kumburu, Neema Penance (Journal of Accounting Research, Organization and Economics, 2025)
Objective This study examines the contributions of Corporate Social Responsibility (CSR) initiatives on educational infrastructure improvements in Tanzanian public primary schools. Using Stakeholder Theory, it identifies discharged CSR initiatives and evaluates their contributions on infrastructure improvements.Design/Methodology A descriptive cross-sectional design was adopted, utilized convergent parallel mixed-methods approach. Quantitative data were collected from 378 respondents, while qualitative data were obtained through key informant interviews and focus group discussions.Results The study found that CSR initiatives significantly improve the availability, adequacy, and status of infrastructure, particularly in the construction of classrooms, toilets, and provision of Teaching and learning materials (p 0.05). However, CSR contributions were limited in improving the teaching and learning environment and misaligned with educational priorities. Critical gaps remain in ICT facilities, fencing, and infrastructure for learners with special needs. It recommends expanding CSR initiatives to include special needs facilities, ICT, and address challenges for sustainable infrastructure improvements.Research limitations/implications The findings are limited to a single district and may not be generalizable across diverse contexts. Future research should explore long-term impacts and scalability.Novelty/Originality This study contributes to the body of knowledge by examining CSR initiatives in education, offering practical, scalable strategies for improving infrastructure in resource-constrained settings.